To solve the equation \(\frac{1}{4}(8 - 16g) + 8 = g\), we will follow these steps:
- Distribute \(\frac{1}{4}\) to the terms inside the parentheses:
\[ \frac{1}{4}(8) - \frac{1}{4}(16g) + 8 = g \]
This simplifies to:
\[ 2 - 4g + 8 = g \]
- Combine like terms on the left side:
\[ 10 - 4g = g \]
- Add \(4g\) to both sides to move all terms involving \(g\) to one side:
\[ 10 = g + 4g \]
This simplifies to:
\[ 10 = 5g \]
- Divide both sides by \(5\) to solve for \(g\):
\[ g = \frac{10}{5} \]
This simplifies to:
\[ g = 2 \]
So the solution to the equation is:
\[ \boxed{2} \]